Atom-dispersed Au combined with nano-Au on halloysite nanotubes with closo-dodecaborate promotes synergistic effects for enhanced photocatalysis. Issue 2 (12th December 2022) - Deng, Xuefan; Yao, Fengze; Wang, Zhengxi; Zhao, Haixu; Qi, Bin; Zhou, Yingtang; Zhang, Haibo; Zhou, Xiaohai
Abstract : Au single atoms (Au SAs) and Au nanoparticles (Au NPs) were obtained on HNT@B12 H12 @Au catalysts. Experimental and theoretical calculations revealed that O–Au–B–Au SAs, O–Au SAs, B–Au SAs and Au NPs are involved in the reaction simultaneously. Abstract : The maximized metal dispersity provided by single-atom (SA) catalysts offers high catalytic activity and selectivity, and maximum metal utilization. However, the lack of adjacent metal atoms in these systems prevents further improvements in intrinsic activity. Here, halloysite nanotubes (HNTs), with their unique charge distribution, are ingeniously combined with the dodecahydro- closo -dodecaborate anion [ closo -B12 H12 ] 2− . Au SAs were synthesized via the reducibility of [ closo -B12 H12 ] 2− and active hydroxyl coordination on the HNT surface. This newly designed material (HNT@B12 H12 @Au) avoids the normally used high-temperature calcination by preparing Au SAs accompanied by Au NPs while keeping an ∼100% Au utilization through the reduction of [ closo -B12 H12 ] 2− and coordination stabilization of HNTs. HNT@B12 H12 @Au showed excellent photocatalytic selective reduction activity for nitrobenzene compounds. Up to 23 kinds of nitrobenzene substrates could be selectively reduced efficiently to corresponding azobenzenes within 2.5 h at room temperature. According to the electron paramagnetic resonance results and theoretical calculations, the photocatalytic properties were further considered at the atomic level, and the underlying mechanism was discussed accordingly. It is concluded that Au NPs and Au SAs have excellent synergistic catalytic effects on photocatalysis precisely because the existence of Au–O and Au–B bonds in HNT@B12 H12 @Au benefits the reaction kinetics.